2001
DOI: 10.1016/s0301-0511(01)00117-x
|View full text |Cite
|
Sign up to set email alerts
|

A psychophysiological analysis of inhibitory motor control in the stop-signal paradigm

Abstract: A psychophysiological analysis of inhibitory motor control in the stop-signal paradigm van Boxtel, Geert; van der Molen, M.; Jennings, J.R.; Brunia, Cees General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
177
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(202 citation statements)
references
References 48 publications
(98 reference statements)
19
177
1
2
Order By: Relevance
“…In an ERP experiment, Anguera and Gazzaley (2012) studied age-related modulations of the N2 and P3 associated with inhibition in a visual Stop-signal task and determined that the older adults' greater SSRT was associated with the P3 latency but not with the P3 amplitude or the N2 latency or amplitude. In their experiment with older adults (N=20; M±SD=70.6±6.7 years old; 9 women), the Stop-signal N2 and P3 were qualitatively comparable to previous ERP studies that used a visual Stop-signal task with young adults (van Boxtel et al 2001;Kok et al 2004;Ramautar et al 2004). However, in contrast with the results that have generally been reported for young adults, the N2 and P3 amplitude was not greater in successful compared with unsuccessful inhibition trials.…”
Section: Age-related Inhibition Changes Between 200 and 400 Mssupporting
confidence: 81%
See 1 more Smart Citation
“…In an ERP experiment, Anguera and Gazzaley (2012) studied age-related modulations of the N2 and P3 associated with inhibition in a visual Stop-signal task and determined that the older adults' greater SSRT was associated with the P3 latency but not with the P3 amplitude or the N2 latency or amplitude. In their experiment with older adults (N=20; M±SD=70.6±6.7 years old; 9 women), the Stop-signal N2 and P3 were qualitatively comparable to previous ERP studies that used a visual Stop-signal task with young adults (van Boxtel et al 2001;Kok et al 2004;Ramautar et al 2004). However, in contrast with the results that have generally been reported for young adults, the N2 and P3 amplitude was not greater in successful compared with unsuccessful inhibition trials.…”
Section: Age-related Inhibition Changes Between 200 and 400 Mssupporting
confidence: 81%
“…Several of these studies have examined the relevance of inhibitory processes in normal aging (Mayas et al 2012;Turner and Spreng 2012;Haring et al 2013;Wostmann et al 2013), as well as a variety of clinical conditions, such as Alzheimer's disease (AD; Collette et al 2009; C. Thomas et al 2010;Cheng et al 2012), mild cognitive impairment (MCI; Belleville et al 2007), traumatic brain injury (TBI; Dimoska-Di Marco et al 2011), depression (Dai and Feng 2011;Bobb et al 2012), anxiety (Robinson et al 2013), schizophrenia (Hughes et al 2012), fibromyalgia (Mercado et al 2013), attention deficithyperactivity disorder (ADHD; Senderecka et al 2012), alcoholism (Padilla et al 2011) and psychopathy (Verona et al 2012). Thomas et al 2009); Stop-signal (Bekker et al 2005;van Boxtel et al 2001);Eriksen Flanker (Wild-Wall et al 2008;Neuhaus et al 2007); Stroop (Hanslmayr et al 2008); and NP (Gibbons et al 2006;Kathmann et al 2006). …”
mentioning
confidence: 99%
“…The processes leading up to response selection in stopsignal and go/no-go paradigms are typically reflected in the N2 and the P3. The N2 was previously linked to response inhibition based on the relationship between its amplitude with inhibition efficiency (van Boxtel, van der Molen, Jennings & Brunia, 2001). However, later studies have shown that it is also present when a response is required, for example when go trials are unexpected or when maximal force go trials are compared with normal force go trials (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…This fi nding is signifi cant because ERP studies examining motor stopping consistently report enhanced N2 components for stopping, such as the no-go N2 (Bekker et al, 2005 ;Bokura et al, 2001 ;Donkers & van Boxtel, 2004 ;Eimer, 1993 ;Falkenstein et al, 1999 ;Garavan et al, 2002 ) and the stop signal N2 (Band & van Boxtel, 1999 ;Logan et al, 1994 ;Schmajuk et al, 2006 ;van Boxtel et al, 2001 ;Ramautar et al, 2004 ) . For example, Mecklinger et al ( 2009 ) found signifi cantly larger N2 for Suppress items in comparison to Respond items, and, importantly found this effect to be especially pronounced for Suppress items that were later forgotten on an independent probe test.…”
Section: Electrophsyiological Indices Of Retrieval Suppressionmentioning
confidence: 99%